Analysis of the Effect of PWHT on the Corrosion Test of API 5L X65 Material in Submerged Arc Welding - Kusminah, Imah Luluk; Anggara, Dika; Wardani, Dianita; Widodo, Eriek Wahyu Restu; Nafi, Maula; Handoko, Lukman; Djati, Anggoro Ludiro; Trianto, Ryo Andika (Eksergi, 2024)
This research discusses the method of making distribution pipes using the Submerged Arc Welding (SAW) welding process, especially for pipes with spiral connections. The material used is API 5L X65. SAW pipes with spiral joints are more commonly used for low-pressure piping systems. However, in certain cases, the production of SAW pipes for Sour Service distribution requires special treatment. Sour Service pipes have a high level of corrosion and residual stress, so Post Weld Heat Treatment (PWHT) is required to prevent Hydrogen Induced Cracking (HIC). HIC occurs due to the absorption and accumulation of hydrogen gas in the metal, causing the formation and growth of cracks, which is also influenced by residual stress. PWHT is applied to reduce residual stress to reduce the risk of corrosion. PWHT is a process to change the structure of the weld metal by heating the metal at a certain temperature and time. This research shows that variations in PWHT temperature produce an average residual stress that is not much different with less difference than 2%, In corrosion testing with the HIC method shows crack evidence but is still satisfactory NACE MR0175 criteria for pipe PWHT temperature variation conditions.